Walter Frank ja taisteleva tiede : aseena Ranskan historia - Komppa, Jukka (1995)
This dissertation seeks to define the concept of "battling science" which was originated by the historian Walter Frank (1905-1945) in the early 1930s. The subject is discussed in relation to Frank's study of late 19th century France, which national socialists esteemed a major historiographical work of their time. In what way did Frank's work refer to battling science, and what accounted for the interest it aroused among national socialists? In both battling science and Frank's historical work, anti-Semitism is brought to the fore. Therefore, this study is also concerned with the extent to which French anti-Semitism, as conveyed by Frank's work, was reflected in German national socialist thinking. To assess this impact, Frank's colleagues' writings on France as well as other relevant contemporary literature is looked into. Although emphasized by national socialists, the battling spirit has been somewhat overlooked by post-war historians. Battling science was strongly associated with Walter Frank's impassioned personality, thus the story of his life also deserves attention in this context. The relevance of battling science to the fighting spirit characterizing Nazism can only be assessed against the background of Frank's career, actions and thinking. Walter Frank's history of France displays the various qualities of an orthodox product of battling science. Frank drew upon his work in the battles he fought in the spheres of politics and politics of science in Germany. The work's usefulness in day-to-day politics was one of the reasons for its high esteem among national socialists. As a phenomenon battling science was inseparable from its times, the period of Hitler's rise to power and consolidation of his position. Walter Frank founded the principles of battling science on the German tradition as exemplified by von Treitschke and, on the other hand, on neoconservatism which emerged in the 1920s. He sought to create an antithesis to liberal historiography dating from the days of the Weimar Republic, and to contemporary emphasis on the subject, represented mostly by university intellectuals. Frank's rejection of intellectualism also shows in his history of France, where Barrès and Maurras exemplified scholars seeking for alternatives to intellectualism. The two French historians appear to have infuenced Frank's thinking, especially his concept of battling science. Frank demanded that, instead of learned people, the writing of history should be directed at the masses as well as political and military leaders. Yet another factor that shaped battling science was Walter Frank's personal position in the German scholarly world at the time of Hitler's rise to power and in subsequent years. Frank eventually lost his hold on historians' professional circles, and he also fell out with his superiors. Ultimately, the principles of battling science were blurred by the imminence of war.